RAMP - risk analysis and management for projects a strategic framework for managing project risk and its financial implications (Thomas Telford, 2005)
Describing the process for analysing and responding to risks which can affect the overall success of projects, this text meets a more rigorous approach to risk management which can be used in a variety of contexts.